DIFFERENTIATION POTENCIES OF EPIBLAST, HYPOBLAST AND PRIMORDIAL GERM CELLS OF CHICK EMBRYO CULTURED IN VITRO - NIM: S2 418808, Arnentis
Abstract: A study on the differentation potencies of epiblast and hypoblast of different stages of chick embryos has been carried out. Blastoderms of chick embryo (Babcock B-7;80) of stage 1-5 (H&H) were used. Of each blastoderm, only the area pellucida was used and was divided into 4 explants (anterior epiblast, posterior epiblast, anterior hypoblast, posterior hypoblast). And were then separately cultured at 37+0,5Âº C for 5 days. Using Wolff and Haffen methode. At the end of the culture period, the explants were fixed using Gendre's solution for 3-4 hours at 4ÂºC, dehydrated with ethanol-nBA solution and imbedded in paraffinwax. Histological sections were stained byPAS-ematoxylin method. The results revealed that axial structures, blood vessels, mesenchyme, embryonic endoderm, yolk sac endoderm and PGC's were differentiated from the anterior as well as posterior epiblast. Stage 1 (H&H) hypoblast (anterior and posterior) differentiated only yolk sac endoderm, while anterior hypoblast of stage 3+-5 (H&H) and posterior hypoblast of stage 3-5 (H&H) differentiated mesenchyme, blood vessels, embryonic endoderm, yolk sacendoderm and PGC's. The number of free PGC's differentiated on stage 1, 2, 3 and 3+ and 5 (H&H) anterior epiblast statistically were not significantly different with each other and were significantly lower than stage 4 (H&H), whereas stage 1, 2, and 3+ (H&H) posterior epiblast were not significantly different and they were significantly lower than stage 4 and 5 (H & H). There were no PGC's differentiated on stage 1 (H & H) hypoblast. The number of free PGC's differensiated on stage 1, 2 and 3 (H&H) anterior hypoblast were not significantly different, they were significantly lower than stage 3+, 4 and 5 (H&H), while the number of PGC's of stage 1 and 2 (H&H) posterior hypoblast were not significantly different and they were significantly lower then stage 3-5 (H&H). The average number of free PGC's differentiated on stage 1-5 (H&H) epiblasts were significantly higher than on the hypoblasts. It could be concluded that chick epiblast and hypoblast are capable to differentiate when cultured separately. Stage 1 & 2 (H&H) anterior as well as posterior epiblast have a higher potency to differentiate embryonic structures than stage 3-5 (H&H) epiblast, whereas stage 3+-5 (H & H) hypoblast have higher differentiation potencies than stage 1, 2 and 3 (H&H). Differentiation potencies of free PGC's are in correlation with the stage of the blastoderm, however the differentiation potency is higher at the epiblast than at the hypoblast.